مملكة الغرامنت وعلاقاتها بالجوار القرن 5 ق.م – القرن 5 م - عبلة سعدان; نــــوال بن خدوج (جامعة الوادي - University of Eloued, 2025)
في ختام هذا البحث، توصلنا إلى مجموعة من النتائج التي تبرز عراقة وقوة مملكة الغرامنت، فقد تمكنت هذه القبائل من تحدي الظروف الصحراوية القاسية، وأسست مملكة متكاملة في فزان لا تزال آثارها قائمة. أظهر الغرامنت عبقرية في الزراعة، من خلال تغطية التربة المالحة بطبقة صالحة للزراعة، كما طوروا نظام ري فعّال باستخدام "الفجارات" لاستخراج المياه الجوفية وتوزيعها عبر قنوات تحت الأرض. أثبتت الدراسات أن الغرامنت كانوا شعبًا أصيلًا في منطقته، عرف بنظام اجتماعي منظم قائم على سلطة الأسرة والقبيلة، ونظام ملكي غير وراثي ينتخب فيه الحاكم من طرف مجلس الشيوخ. كما كان للغرامنت جيش قوي ومنظم، شمل المشاة والفرسان ووحدات خاصة، وابتكروا العربة الحربية الطائرة. امتهن السكان الزراعة والرعي والصيد، ودجّنوا الحيوانات لتخدم حاجاتهم. ولعب موقع جرمة الجغرافي دورًا تجاريًا محوريًا، إذ ربط بين شمال إفريقيا وجنوبها، ما مكنها من تصدير منتجاتها إلى مناطق بعيدة كقرطاج ومصر. عُرف الغرامنت بهويتهم الواضحة ولباسهم المميز، وكانت لهم علاقات خارجية تراوحت بين السلم والعداء، خاصة مع الاحتلال الروماني، الذي تمردوا عليه مرارًا، رغم فترات السلم التي سادت أحيانًا. وبالرغم من التحديات، تمكن الغرامنت من تأسيس مملكة ذات مكانة وهيبة، حظيت باهتمام المؤرخين القدامى، ما يعكس أهميتها في تاريخ المنطقة. "At the conclusion of this research, we arrived at a set of findings that highlight the richness and strength of the Garamantian Kingdom. These tribes succeeded in overcoming the harsh desert conditions and established a fully structured kingdom in Fezzan, whose remnants still stand today. The Garamantes demonstrated ingenuity in agriculture by covering salty soil with fertile layers, and they developed an efficient irrigation system known as foggara to extract and distribute groundwater through underground channels, reducing evaporation in the region’s extreme heat. Studies confirm that the Garamantes were an indigenous people, deeply rooted in their land, with a well-structured social system based on the authority of the family and tribe, and a non-hereditary monarchy where kings were elected by a council of elders. They also formed a strong and organized army, comprising infantry, cavalry, and specialized units, and even invented a flying war chariot. The inhabitants practiced agriculture, herding, hunting, and animal domestication according to their needs, using dogs, livestock, donkeys, camels, and horses. The central location of Garama in the Sahara made it a key trade hub linking North and Sub-Saharan Africa, enabling the export of local and imported goods to coastal cities and even distant places like Carthage and Egypt. The Garamantian society was marked by a clear identity and distinctive attire, and their foreign relations ranged from peaceful coexistence to conflict, especially with the Roman Empire, against which they frequently rebelled, although periods of peace did occur, facilitating trade. Despite the difficult environment, the Garamantes managed to establish a powerful and respected kingdom, recognized for its significance and legacy, which drew the attention of many ancient historians.
مذكرة ماستر قسم علوم انسانية تخصص تاريخ الحضارات القديمة
Keywords: قبائل مملكة الغرامنت; العلاقات العسكرية; فران; مملكة الغرامنت; Kingdom of Garamantes; Fran; military relations; tribes of the Kingdom of Garamantes